Fungsi Kehumasan Badan Perpustakaan Provinsi Bengkulu Dalam Meningkatkan Minat Kunjung Dan Gemar Membaca - Septa Agustina (Professional: Jurnal Komunikasi dan Administrasi Publik, 2017)
This study aims to determine the " Field Service Strategy ( PR function ) Library Board of Bengkulu province in increasing interest and love reading itinerant " , as well as to know the constraints faced by the field service visits increase interest in and love to read . This study uses the concept of management " process four main stages " of Scot M.Cutlip and Allen H. The Center for Research and Listening , Planning and Decision Makers , Communicating and Implementation ,Assessment . Data collection in this study used interview techniques , observation , documentation and literature . Key informant interviews were conducted to the local library service field staff , and the principal informant visitors who visit the library . Analyzed using qualitative data through the stages of data reduction , data display , conclusion. The results showed that ( 1 ) the service area of ​​the library board strategy Bengkulu province in increasing interest and love reading visit is to establish the village library and adds library collection materials each year . ( 2 ) The contents of the messages used Bengkulu library service areas are invited to have a love reading because the reading will add to the knowledge and window to the world . ( 3 ) the implementation of media strategies that used the local library is not maximized because it is constrained by limited funding . As for the major constraint in increasing interest and love reading go by the library staff is limited funding.